Socio-Economic Conditions of the Fishing Community in Nuwewang Village, Letti District, Maluku Barat Daya Regency - Rakuasa, Heinrich; Letedara, Reindino`; Darisera, Stiadi; Sipiel, Roni (Sinergi International Journal of Economics, 2023)
This research aims to analyze the various social and economic aspects that influence the lives of the fishing community in the village. Through field surveys, data collection and qualitative analysis, this article reveals an in-depth picture of the social and economic dynamics in the Nuwewang fishing community. This research was conducted in Nuwewang Village, Letti Sub-district, Southwest Maluku Regency. The population in the study was 60 family heads and the sample in the study was 20 fishermen. This type of research is quantitative descriptive research. The data collection techniques used in this research are observation, documentation, interview techniques using questionnaires for data collection. The results showed that fishing communities in Nuwewang Village face various challenges in social and economic aspects. Economically, they face limited access to markets, equipment and capital which limits their income potential. These factors directly affect their standard of living and economic welfare. On the social side, factors such as education, access to healthcare and infrastructure are also serious issues that affect the quality of life of fishing communities. This research contributes to the understanding of the socioeconomic challenges faced by fishing communities in this area. The findings can serve as a basis for designing policies that support welfare improvement and economic empowerment for fishing communities in Nuwewang Village and similar areas. Efforts to improve access to markets, education, health services and capital support could be important steps in improving socioeconomic conditions.